Preparation and characterisation of ciprofloxacin‐loaded silver nanoparticles for drug delivery - Samer Hasan Hussein‐Al‐Ali; Suha Mujahed Abudoleh; Qais Ibrahim Abdallah Abualassal; Zead Abudayeh; Yousef Aldalahmah; Mohd Zobir Hussein (IET Nanobiotechnology)
Abstract Silver nanoparticles (AgNPs) have shown potential applications in drug delivery. In this study, the AgNPs was prepared from silver nitrate in the presence of alginate as a capping agent. The ciprofloxacin (Cipro) was loaded on the surface of AgNPs to produce Cipro‐AgNPs nanocomposite. The characteristics of the Cipro‐AgNPs nanocomposite were studied by X‐ray diffraction (XRD), UV–Vis, transmission electron microscopy (TEM), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), Fourier‐transform infra‐red analysis (FT‐IR) and zeta potential analyses. The XRD of AgNPs and Cipro‐AgNPs nanocomposite data showed that both have a crystalline structure in nature. The FT‐IR data indicate that the AgNPs have been wrapped by the alginate and loaded with the Cipro drug. The TEM image showed that the Cipro‐AgNPs nanocomposites have an average size of 96 nm with a spherical shape. The SEM image for AgNPs and Cipro‐AgNPs nanocomposites confirmed the needle‐lumpy shape. The zeta potential for Cipro‐AgNPs nanocomposites exhibited a positive charge with a value of 6.5 mV. The TGA for Cipro‐AgNPs nanocomposites showed loss of 79.7% in total mass compared to 57.6% for AgNPs which is due to the Cipro loaded in the AgNPs. The release of Cipro from Cipro‐AgNPs nanocomposites showed slow release properties which reached 98% release within 750 min, and followed the Hixson–Crowell kinetic model. In addition, the toxicity of AgNPs and Cipro‐AgNPs nanocomposites was evaluated using normal (3T3) cell line. The present work suggests that Cipro‐AgNPs are suitable for drug delivery.